Effec Of Low Protein Diet On Chronic Renal Failure Due To Autosomal Dominant Polycystic Kidney Disease - Terukuni Ideura; Takeo Kanno; Miyuki Shimazui; Hiroyuki Morita (The Korean Society of Nephrology, 2012)
There are few reports about therapeutic effects of low protein diet on the progression of chronic renal failure due to autosomal dominant polycystic kidney disease (ADPKD), although the disease is common.The annual incidence rate for end-stage renal disease caused by ADPKD is around 6 per million.In this retrospective study in one center, ten chronic renal failure patients due to ADPKD with creatinine clearnce of 17.0±3.3 mL/min /1.73 m2 and serum creatinine (Cr) level of 4.4±0.7 mg/dL were studied for 40 months after the introduction of severe low protein diet (SLPD) (0.48±0.03 g/kgBW/day) without supplementation of essential amino acids or keto-analogues. Dietary protein intake was estimated by urea appearance rate from 24hr urine sample according to Mitch-Maroni's formula. The results clearly showed that ▵1/Cr/month(×10−3) was significantly suppressed from 5.8±0.9 to 2.0±0.6 following the introduction of SLPD (p<0.02). Furthermore, BUN/Cr ratio decreased from 10.4±0.02 to 7.3±0.02 (p<0.01). Mean blood pressure (mmHg) remained unchanged; 92±3 vs 89±3 (ns), and urinary protein excretion (g/day) did not change; 0.6±0.2 vs 0.6±0.1 (ns). There were no significant differences between body mass index, serum albumin, transferrin and hemoglobin levels as the indices of nutritional state before and after the introduction of SLPD.In conclusion, SLPD was effective in suppressing the progression of further decline in renal function due to ADPKD under nutritionally safety condition in this cohort.